2006
DOI: 10.1007/s00380-005-0885-x
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural statin therapy reduces the risk and extent of cardiac biomarker release following percutaneous coronary intervention

Abstract: This study evaluates the association between statin therapy in patients treated by percutaneous coronary intervention (PCI) for stable angina pectoris and postinterventional myocardial injury with subsequent long-term clinical outcome. Prospectively collected data on 400 consecutive patients with stable angina pectoris or evidence of inducible myocardial ischemia were analyzed. The incidence of myocardial infarction based on postinterventional release of troponin I>1.5 ng/ml was 12% in the statin pretreated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…These pleiotropic effects may potentially improve outcome after PCI. Many studies were demonstrated that early statin therapy among PCI patients is associated with significant mortality and morbidity advantages in different patient subsets [1][2][3][4][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These pleiotropic effects may potentially improve outcome after PCI. Many studies were demonstrated that early statin therapy among PCI patients is associated with significant mortality and morbidity advantages in different patient subsets [1][2][3][4][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Many studies have demonstrated that early statin therapy among PCI patients is associated with significant advantages for decreased mortality and morbidity in different patient subsets. 10,[26][27][28] Although the mechanism is not entirely clear, the anti-inflammatory effects of statins might contribute to the reduced myocardial injury during PCI. In the present study, prior statin therapy had no significant effect on postprocedural troponin elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Significant benefit of statin pre-therapy on periprocedural elevation of Troponin-Iwas also demonstrated in many studies. [11][12][13][14] In this study incidence of cTn-I rise following PCI was 86% without atorvastatin pretreatment and 10% with atorvastatin pretreatment. So the incidence of myonecrosis is less in atorvastatin pretreated group and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 50%